2022
DOI: 10.1172/jci.insight.157342
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram inhibits neutrophil extracellular trap formation and protects rodents from acute lung injury and SARS-CoV-2 infection

Abstract: Severe acute lung injury has few treatment options and a high mortality rate. Upon injury, neutrophils infiltrate the lungs and form neutrophil extracellular traps (NETs), damaging the lungs and driving an exacerbated immune response. Unfortunately, no drug preventing NET formation has completed clinical development. Here, we report that disulfiram -an FDAapproved drug for alcohol use disorder-dramatically reduced NETs, increased survival, improved blood oxygenation, and reduced lung edema in a transfusion-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 89 publications
(130 reference statements)
1
55
0
Order By: Relevance
“…As already discussed, NET formation is a prominent feature of lung pathology in the SAS-CoV-2 infection. Using a rodent infection model of SARS-CoV-2, it has been shown that disulfiram can significantly reduce NET formation and increase survival demonstrating its therapeutic potential [ 263 ]. As disulfiram is FDA approved and is well-tolerated clinically, it is well poised for translation to treat NET-driven pathologies.…”
Section: Potential Therapy Targeting the Injurious Functions Of Extra...mentioning
confidence: 99%
“…As already discussed, NET formation is a prominent feature of lung pathology in the SAS-CoV-2 infection. Using a rodent infection model of SARS-CoV-2, it has been shown that disulfiram can significantly reduce NET formation and increase survival demonstrating its therapeutic potential [ 263 ]. As disulfiram is FDA approved and is well-tolerated clinically, it is well poised for translation to treat NET-driven pathologies.…”
Section: Potential Therapy Targeting the Injurious Functions Of Extra...mentioning
confidence: 99%
“…However, it has been identified that disulfiram is covalently targeted on human/mouse Cys191/Cys192 of GSDMD protein leading to blocking the GSDMD pore formation, IL-1β release, and pyroptosis ( 98 ). Furthermore, another study showed that disulfiram can inhibit the NET formation and protect rodents from SARS-CoV-2 infection ( 101 ). All these raise a common point that one drug/compound might target various proteins even on multiple signaling pathways to either synergically exert effects or trigger off-target toxicities.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Here, we emphasized the Food and Drug Administration (FDA)-approved alcoholism-averting drug, disulfiram, which was identified as an inhibitor of GSDMD pore formation by covalently modifying human/mouse Cys191/Cys192 in GSDMD and preventing IL-1β release and pyroptosis ( 98 ). Although the linkage of GSDMD-mediated pyroptosis with NETosis has been reported ( 99 , 100 ), Egeblad and colleagues recently found that treatment with disulfiram reduced NET formation, as well as lung inflammation and perivascular fibrosis in a golden hamster SARS-CoV-2 infection model via downregulated innate immune and complement/coagulation pathways ( 101 ).…”
Section: Multiple Cell Death Pathways Were Induced In Sars-cov-2 Infe...mentioning
confidence: 99%
“…Moreover, Adrover et al demonstrated that DSF under experimental conditions appeared to confer more benefits on lung pathology in SARS-CoV-2-infected hamsters than dexamethasone, widely used for COVID-19 treatment. The authors also showed that dexamethasone, but not DSF, significantly increased the viral load in the lungs when administered from day 1 post-infection [ 114 ]. It is worth adding that many authors warn against the unfavorable effects of corticoid therapies on respiratory viruses [ 115 ].…”
Section: Disulfiram In Covid-19 Treatmentmentioning
confidence: 99%